Resolution based on the results of the V annual scientific-practical conference "RWD/RWE. Possible and real" - A. S. Kolbin; M. A. Borzova; D. Yu. Belousov; V. V. Kalinichenko (Реальная клиническая практика: данные и доказательства, 2024)
On September 19, 2024, in Moscow (Russian Federation), the V annual scientific-practical conference with international participation "RWD/RWE. Possible and Real" were organized and held. The theme of the conference brings together leading experts in RWD and RWE fields. The participants of the conference discussed the research tools of RWD/RWE, the confirmed value of RWE in modern medicine, legislation, and global perspectives worldwide, including the Russian Federation and the EAEU. A total of 28 reports were heard at the conference. Based on the results of the conference, a Resolution was developed, the text of which we offer you to familiarize yourself with.